2015
DOI: 10.1210/en.2015-1226
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss After RYGB Is Independent of and Complementary to Serotonin 2C Receptor Signaling in Male Mice

Abstract: Roux-en-Y gastric bypass (RYGB) typically leads to substantial, long-term weight loss (WL) and diabetes remission, although there is a wide variation in response to RYGB among individual patients. Defining the pathways through which RYGB works should aid in the development of less invasive anti-obesity treatments, whereas identifying weight-regulatory pathways unengaged by RYGB could facilitate the development of therapies that complement the beneficial effects of surgery. Activation of serotonin 2C receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Others reported that RYGB rats lost additional weight when treated with serotonin 2C-receptor agonists (Carmody et al, 2015), and ate more and gained weight when treated with a melanocortin 3- or 4-receptor antagonist (Mumphrey et al, 2014) and temporarily ate more after a period of food restriction during which they lost additional weight (Lutz and Bueter, 2014). Thus, a variety of eating-control mechanisms remain functional after RYGB in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that RYGB rats lost additional weight when treated with serotonin 2C-receptor agonists (Carmody et al, 2015), and ate more and gained weight when treated with a melanocortin 3- or 4-receptor antagonist (Mumphrey et al, 2014) and temporarily ate more after a period of food restriction during which they lost additional weight (Lutz and Bueter, 2014). Thus, a variety of eating-control mechanisms remain functional after RYGB in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated wild-type mice that were part of a larger study examining the effects of 5HT2C-receptor on metabolism after RYGB (29). Male C57BL/6J mice (Jackson Labs, Bar Harbor, ME) were placed on a 60% high fat diet (HFD; Research Diets, D12492) at weaning to induce substantial obesity.…”
Section: Methodsmentioning
confidence: 99%
“…Face to these intriguing results, we were led to raise the question of an eventual fecal loss of energy to account for the prolonged body weight loss in absence of prolonged decrease in food intake and its maintenance during food recovery, as observed in ours [30] and others [[9], [10], [11], [12], [13], [14],16,17,19,20,39] studies. Indeed, another common feature of the literature on gastric bypass in mice is that the surgery induces a strong decrease in body weight under high calorie diets, but is pretty ineffective under standard diet conditions [30,37,38].…”
Section: Discussionmentioning
confidence: 86%
“…For example, the role of the melanocortin system was questioned later [18]. This also relates to the eventual implications of various hormones (including gastrointestinal ones but not only) as fibroblast growth factor 21, peptide YY or glucagon-like peptide 1 (GLP-1), or their receptors as leptin receptor, serotonin 2C receptor, GLP-1 receptor, Y2 receptor [[9], [10], [11], [12], [13], [14],16,17,19,20,39], or other receptors putatively involved in RYGB beneficial effects as the bile acid receptor TGR5 or mu-opioid receptors [14,30] that all concluded that the tested hormone or receptor is dispensable for the metabolic effects of gastric bypass in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation